1975
DOI: 10.1111/j.1524-4725.1975.tb00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Histographic Surgery: Accuracy of Visual Assessment of the Margins of Basal‐Cell Epithelioma

Abstract: Mohs' chemosurgery, with its complete microscopic control, is the most reliable procedure in achieving complete ablation of basal‐cell epitheliomas on the face. By utilizing this method, we compared basal‐cell epitheliomas treated by histographic surgery both as to the clinically estimated extension and as to the actual size of the defect resulting from complete tumor removal. This paper deals with the question of how broad a margin of normal tissue should be included in the excision of tumors of varying sizes. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
5

Year Published

1983
1983
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(79 citation statements)
references
References 11 publications
(12 reference statements)
1
73
0
5
Order By: Relevance
“…3 The clinically visible tumor surface may only represent one fifth of its local microscopic invasion. 4 Therefore, identification of high-risk lesions with extensive subclinical spread can help determine optimal treatment and can significantly reduce morbidity and cost.…”
mentioning
confidence: 99%
“…3 The clinically visible tumor surface may only represent one fifth of its local microscopic invasion. 4 Therefore, identification of high-risk lesions with extensive subclinical spread can help determine optimal treatment and can significantly reduce morbidity and cost.…”
mentioning
confidence: 99%
“…This technique assumes tumour growth only follows a perfectly spherical or elliptical pattern and may lead to false-negative results ( Figure 5). Research data from studies examining subclinical extension using microscopic control of complete lateral and deep margins has shown that an asymmetrical subclinical growth pattern with one or multiple extensions appears to characterize the majority of BCCs (24)(25)(26). Standard frozen section techniques have been found to be accurate in only 72% of cases (27).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, excisions were performed 1 mm beyond the 3-mm margin of treatment, and all excisional margins were negative, so a 4-mm margin of treatment beyond the lesion would have been sufficient for all skin cancers in our series. Larger BCCs and SCCs (Ͼ2 cm) are likely to have a greater radius of subclinical extension, 31,33,36 and greater treatment margins are recommended.…”
Section: Commentmentioning
confidence: 99%
“…Current recommendations for excisional margins for primary nonmorphea-form BCC range from 2 to 5 mm. [30][31][32][33][34][35][36] Wolf and Zitelli 33 demonstrated subclinical extension that was sufficiently excised using 4-mm margins in 95% of BCCs smaller than 2 cm. No data specifically address subclinical extension in superficial BCC.…”
Section: Commentmentioning
confidence: 99%